Quality of Life in Breast Cancer Patients Treated With Mistletoe Extracts: A Systematic Review and Meta-Analysis - Martin Loef PhD; Daniela Paepke MD; Harald Walach PhD, PhD (Integrative Cancer Therapies, 2023)
Background: Breast cancer is the most common cancer type in women and quality of life an essential part of patients’ well-being. Although the treatment with mistletoe extracts is covered by multiple cancer guidelines and reviews, it is uncertain whether mistletoe extracts can improve the quality of life in breast cancer patients. We therefore performed a systematic review and meta-analysis on this topic. Methods: This systematic review included randomized clinical trials (RCTs) and non-randomized studies of intervention (NRSIs) comparing the quality of life in breast cancer patients treated with mistletoe extracts as add-on therapy to control groups treated conventionally. We searched previous systematic reviews and multiple databases until January 2023. We conducted a meta-analysis and assessed the risk of bias according to the Cochrane Handbook via RoB 2 and ROBINS-I and the certainty of evidence via GRADE, respectively. Results: Nine RCTs and 7 NRSIs with 833 and 2831 participants, respectively, were included. The pre-post changes for the quality of life resulted in a pooled standardized mean difference for RCTs of SMD = 0.61 (95% CI 0.47-0.75; P  < .0001) and for retrospective NRSIs of SMD = 0.46 (95% CI 0.10-0.82; P  = .01). The risk of bias was low to high for the RCTs and serious for all NRSIs. The certainty of evidence was moderate for RCTs and very low for NRSIs. Discussion: Our results indicate a clinically relevant, medium-sized effect of mistletoe extracts on the quality of life in breast cancer patients which may be based on the immunomodulating effects of mistletoe extracts during chemotherapy. The limitations of evidence include the risk of bias which is mainly caused by the difficulty of blinding. Further RCTs and real-world evidence need to confirm this result, especially in the setting of neoadjuvant chemotherapy and in breast cancer survivors.